2014
DOI: 10.1016/j.energy.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Modelling tools to evaluate China's future energy system – A review of the Chinese perspective

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…Previous studies have found that BU and TD models demonstrate wide ranges of future energy and emission trajectories at both global and national levels [3][4][5]25]. For example, [45] found that TD models typically indicate larger macroeconomic costs as the consequence of a given mitigation policy.…”
Section: How Big Is the Gap -Comparison Of Results With Leading Globamentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found that BU and TD models demonstrate wide ranges of future energy and emission trajectories at both global and national levels [3][4][5]25]. For example, [45] found that TD models typically indicate larger macroeconomic costs as the consequence of a given mitigation policy.…”
Section: How Big Is the Gap -Comparison Of Results With Leading Globamentioning
confidence: 99%
“…1). This methodology builds on our previous work, which was limited in scope and tested only for the China regions in both models [25]. In this study we expand and document the iterative soft-linking methodology for these two global models and discuss our scenario assumptions for a subsequent model comparison with a focus on China.…”
Section: Soft-linking Two Global Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing pathways for China's future development and associated global issues relies on complex global modelling tools that incorporate sufficient sub-regional details of China. Recent modelling exercises that account for such global and sub-regional economy and energy system features are however rarely described in the peer-reviewed academic literature (Mischke and Karlsson 2014). This China soft-linking case study aims to bridge this knowledge gap between existing global and China-specific scenario studies, which are currently carried out by different academic institutions with multiple modelling tools (Mischke and Karlsson 2014).…”
Section: From Global Modelling To Country Analysis: Focus On China Wimentioning
confidence: 99%
“…Interestingly, Input-Output (IO) models were often used in combination with CGE or PE models, either as alternative to LCA or to strength the overall LCI for some specific technologies (see e.g., Dandres et al, 2012;Earles et al, 2013;Lee and Lee, 2008). Lee and co-authors (2011) and Mischke and Karlsson (2014) comprehensively illustrate the pros and cons of using CGE, PE, LCA and IO models to predict the environmental impacts at country's scale. On the one hand, CGE models are considered beneficial to provide with information to simulate the response of the full economy to certain policy scenarios, incorporating price changes at the level, for example, of IO tables.…”
Section: Introductionmentioning
confidence: 99%